(untitled) (SCIENCE TIME JOURNAL, 2026)
English for Specific Purposes (ESP) has become increasingly important in higher education due to the growing demand for discipline-specific language competence. However, ESP course design in humanities faculties often lacks sufficient consideration of authentic reading practices and disciplinary literacy needs. This study investigates the actual reading materials, strategies, and linguistic challenges encountered by students and instructors in History and Psychology faculties through a mixedmethods needs analysis. Quantitative data were collected using questionnaires administered to undergraduate students and faculty members, while qualitative insights were obtained through semistructured interviews and document analysis of course materials. The findings reveal significant differences between the two disciplines regarding text types, vocabulary density, citation styles, and reading purposes. History students predominantly engage with archival documents, historical narratives, and historiographical analyses, whereas Psychology students frequently read empirical research articles, case studies, and statistical reports. Despite disciplinary variations, both groups identified academic vocabulary, complex sentence structures, and critical interpretation as major reading difficulties. The study highlights the necessity of discipline-sensitive ESP curricula that incorporate authentic materials and targeted reading strategies. The article concludes that integrating actual academic reading practices into ESP instruction can improve students’ comprehension, motivation, and academic performance within humanities education.